Art 2131 Optimization Of Gold Installment Financing Akad Murabahah Agreement In Order To Improve Sharia Financial Inclucion At Bank Sharia Indonesia Meurah Dua District, Pidie Jaya Regency - Baihaqi (Al Mashaadir : Jurnal Ilmu Syariah, 2026)
This study aims to analyze the optimization of gold installment financing through the murabahah contract to increase Islamic financial inclusion at Bank Syariah Indonesia (BSI) in Meurah Dua District, Pidie Jaya Regency. The method used was a qualitative case study approach. Data were collected through in-depth interviews with internal bank personnel and various community members as customers. The results indicate that gold installments at BSI are a financing facility for gold bullion ownership with an installment system that utilizes the murabahah contract for buying and selling and the rahn contract for collateral. This product offers tenors of 1 to 5 years with a minimum weight starting from 0.05 grams. Field findings revealed that people use this product as a long-term, inflation-resistant investment instrument (a safe haven), a strategy for financing children's education, and as a way to prepare for wedding dowries. The 0% installment scheme at BSI Meurah Dua acts as a "positive force" in fostering family financial discipline. Overall, this product effectively supports increasing Islamic financial inclusion by reaching segments of society that previously had difficulty accessing formal financial services (the unbanked).